P11.66.A Immune checkpoint inhibitors related peripheral nerve disorders: clinical and electrophysiological particularities. (5th September 2022) - Birzu, C; Farina, A; Pegat, A; Devic, P; Lenglet, T; Viala, K; Debs, R; Fargeot, G; Picca, A; Le Guennec, L; Mongin, M; Villette, B; et al.
Abstract: Background: The immune-checkpoint inhibitors (ICIs) announced a new era in cancer treatment allowing long-term survival in advanced cancers. However, immune related adverse events impose treatment limitations being one of the main challenges when dealing with ICI treated patients. Neurologic toxicities have unique presentations and can progress rapidly, requiring prompt recognition. Among them, ICI-related peripheral nerve disorders are highly heterogeneous, profoundly debilitating, and insufficiently explored. Material and Methods: We reviewed the clinical and electrodiagnostic features of a retrospective cohort of patients hospitalized in our centre for ICI related neuropathies. We applied the EFNS 2021 electrodiagnostic criteria for neuropathies and we researched the outcome according to the treatment received. Results: We included 16 patients: 4 men and 12 women, median age 61 years (31-72) treated by anti-PD1 monotherapy (10) or antiCTLA4-antiPD1 combination (6). Median delay from ICIs initiation to neuropathy symptoms was 58, 5 days (4 cycles), it seemed lower in combination group (median 33, 5 days vs 81, 5 days in monotherapy patients p=0, 02). Half of patients presented with concurrent non-neurological irAE. CSF was inflammatory in 56% of cases, pleocytosis was seen in 57% of these. Cranial nerve involvement was rare (3/16) the most frequent phenotype was demyelinating polyneuropathy fulfilling EFNS 2021 EMG criteria in 10 cases. The other 6 presented with non-length dependent sensory neuropathy, (3) dysautonomic neuropathy (1) or sensory motor neuropathy with incomplete EFNS 2021 EMG criteria (2). ICI treatment was stopped, and steroids were the first line of treatment for all patients. However, 12/16 patients received additional iv immunoglobulin. Supplementary immunomodulation (cyclophosphamide, tocilizumab) was required in 2 cases. 75% of patients improved within a median of 4.5 months, median decrease in mRS was 2 points. Noteworthy, the rechallenge by antiPD1 monotherapy was proposed in 4 patients with a single neuropathy relapse. Conclusion: Our series expand the knowledge on the clinical and electrophysiological phenotype of ICI related neuropathies improving their recognition in clinical practice. Moreover, our findings argue for the benefit of adding iv immunoglobulin to steroids as a first line treatment for different phenotypes of ICI related neuropathies.